Exiting Detroit for school: inequitable choice sets and school quality. Issue 4 (4th July 2022) - Lenhoff, Sarah Winchell; Singer, Jeremy; Pogodzinski, Ben; Cook, Walter
ABSTRACT: Research has documented the complexity of parent decision-making within school choice marketplaces, including the ways in which individual preferences, social networks, and geography influence where parents choose to enroll their children in school. Yet, parent choices are constrained by the ways in which these dynamics intersect with existing school characteristics and locations. By constructing unique choice set 'landscapes' for 194 Detroit neighborhoods, taking into account where current neighbors attend school in the city, this paper contributes new evidence on the influence of peer enrollment on school choosing, and how peer choice sets differ from students' nearest schools. We find that parents are responsive to lower quality schools in their choice sets when choosing to exit and that choice set quality varies by race, with Black students having lower quality schools in their Detroit choice sets.